Designing Podcast for the Teaching of Islamic Expressions in English - Afdhila Khusnila Wati; Dedi Irwansyah (EDULANGUE, 2020)
The use of podcast as a medium of instruction in English classrooms has gained immense interests of L2 researchers and practioners. However, few of the existing studies highligt the use of Podcast to teach Islamic expressions within the context of Indoesian Islamic higher education. To fill this gap, this study aimed at designing Podcast that serves purposes for the teaching of Islamic expressions in English, and documenting the students’ perceptions toward the instructional design. This case study garnered the data from 45 students majoring in the English Department at the State Islamic Institute of (IAIN) Metro, Indonesia. The empirical evidence show that designing the Podcast for the teaching of Islamic expressions in English requires four interplay and systematic steps, namely planning, designing, evaluating, and uploading. The students perceived that their acceptance to the Podcast based learning design was driven by two key factors, namely the moral values embedded in the podcasts addressing Islamic content, and the content delivery fitting the condition of the target audience. This study encapsulates that English teachers pay attention on the content and pedagogical methods when designing a Podcast for the teaching of Islamic expressions in English.